Law and Health: What are the Legal Aspects of BPJS Participants during the Covid 19 Pandemic - Elli Ruslina (Enrichment : Journal of Management, 2020)
Article 28 H paragraph (1) of the 1945 Constitution which reads "everyone has the right to live in physical and spiritual prosperity, to live and to have a good and healthy life and have the right to obtain health services". Quality health services in question are health services in emergencies and disasters, health services that meet the needs of the community and are carried out in accordance with professional standards and ethics. Based on Law no. 40 of 2004 concerning Insurance and Law no. 24 of 2011 concerning the Social Security Administering Body, BPJS was formed which is an institution established to administer the National Social Security program and the BPJS Health program which aims to provide certainty of social protection and welfare for all Indonesian people. A survey conducted by the Center for Population Research (2019) in six provinces related to “Utilization of National Health Insurance” found that 24.5% of informal sector workers claimed to have experienced BPJS Health contributions in arrears, with an average length of arrears of six months. In fact, 6.9% of informal sector workers have BPJS Health cards in an inactive condition for the last 6 months. The results of this survey also indicate that under ordinary conditions it is difficult for informal sector workers to pay contributions for independent BPJS participants, especially in the current COVID-19 pandemic conditions, it is certain that more and more informal sector workers will be in arrears in premiums and some may even drop out. The research approach uses secondary data (library research), which is a method used by studying statutory documents, books and articles in journals related to the discussion material in the covid 19 pandemic. The purpose of the study is to examine and analyze how the Legal Aspects of BPJS Health Participants in In the era of the Covid 19 Pandemic and to study and analyze how can it be said that it is force majeure for participants who are unable to carry out their agreement?